2022
DOI: 10.1038/s41598-022-20679-6
|View full text |Cite
|
Sign up to set email alerts
|

Iron status and the risk of sepsis and severe COVID-19: a two-sample Mendelian randomization study

Abstract: Observational studies have indicated an association between iron status and risk of sepsis and COVID-19. We estimated the effect of genetically-predicted iron biomarkers on risk of sepsis and risk of being hospitalized with COVID-19, performing a two-sample Mendelian randomization study. For risk of sepsis, one standard deviation increase in genetically-predicted serum iron was associated with odds ratio (OR) of 1.14 (95% confidence interval [CI] 1.01–1.29, P = 0.031). The findings were supported in the analys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 58 publications
0
9
1
Order By: Relevance
“…This may indicate that several of these micronutrients are not important risk factors for the infections considered. Finally, high levels of serum iron have in previous MR studies been associated with skin and soft tissue infections and sepsis, but we did not find any evidence of an association for the infections that we considered [58,59]. This discrepancy may be due to organ-specific effects of iron (e.g., iron levels were also associated with damages to skin-related structures) and that the infectious diseases are not comparable (e.g., sepsis is an inflammatory syndrome in response to severe infection) [59,60].…”
Section: Discussioncontrasting
confidence: 68%
“…This may indicate that several of these micronutrients are not important risk factors for the infections considered. Finally, high levels of serum iron have in previous MR studies been associated with skin and soft tissue infections and sepsis, but we did not find any evidence of an association for the infections that we considered [58,59]. This discrepancy may be due to organ-specific effects of iron (e.g., iron levels were also associated with damages to skin-related structures) and that the infectious diseases are not comparable (e.g., sepsis is an inflammatory syndrome in response to severe infection) [59,60].…”
Section: Discussioncontrasting
confidence: 68%
“…The analysis did not show reliable evidence of any plausible significant associations of micronutrients’ status and vulnerability to infection or COVID-19 severity [21 ▪▪ ]. This finding was corroborated for vitamin C [22,23], but not for iron, for which higher genetically predicted status had been associated with sepsis [24].…”
Section: Micronutrients and Coronavirus Disease 2019mentioning
confidence: 82%
“…Our data show a possible connection between the redox imbalance reported in COVID-19 and long-COVID and altered iron metabolism. Interestingly, it has been reported that susceptibility to viral infection with HIV, H1N1, SARS, and COVID-19 is associated with iron levels [129][130][131], and increased plasma levels of free iron correlate with adverse outcomes for COVID-19 patients [132,133]. Previous studies have demonstrated the antiviral effects of iron-chelators, such as deferoxamine (DFO) or deferiprone, for HIV, HSV-1, and CMV [56,57,134,135], and iron chelation therapies are shown to be effective in the management of COVID-19 patients by decreasing the production of free radicals and reducing IL-6 levels [129,136].…”
Section: Discussionmentioning
confidence: 99%